(untitled) (Perner’s Contacts, 2014)
The article describes state of implementation Integrated management system in the companies operating railway passenger transport in European Union. The paper describes the possibility of application Lean philosophy in the sector of transport services in order to eliminate any type of wastage. The result of this elimination is general improvement of processes and increase of quality provided services in mentioned area.